First Study of Ascaris lumbricoides from the Semiwild Population of the Sumatran Orangutan Pongo abelii in the Context of Morphological Description and Molecular Phylogeny - Civáňová Křížová, Kristína; Seifertová, Mária; Baruš, Vlastimil; Hodová, Iveta; Mašová, Šárka; Nurcahyo, Wisnu; Foitová, Ivona (Life (Basel, Switzerland), 2023)
There is little evidence that the already described and accepted taxa of ascarids (Ascaris lumbricoides, A. suum, and A. ovis) infecting individuals of taxonomically distant groups (hominids, pigs, sheep, goats, and dogs) can be genetically or morphologically distinguished. However, despite described morphological differences, e.g., due to intraspecific variation, these are insufficient for species determination and may indicate differences amongst ascarids because of cross infections, hybrid production, and specific adaptations to hosts. Herein, the results of a molecular and morphological analysis of ascarids parasitising Sumatran orangutans (Pongo abelii Lesson, 1827) in native populations are presented. The research took place in the Bukit Lawang area, Indonesia, in 2009. Throughout the year, fresh faecal samples were collected regularly from 24 orangutans, and all were examined for the presence of nematode adults. Only five adult worms from two orangutan females were found during regular collection. Using the integrative taxonomic approach, the nematodes found were identified as A. lumbricoides. The significance of the find and its rarity is documented by the fact that this is the first confirmed finding of adult ascarids from an original orangutan site (not from a zoo) in more than 130 years (including the long-term study spanning the last 20 years focusing on orangutan parasites and natural antiparasitic drugs). More accurate morphometric parameters and genetic differences for the identification of ascarids were established. These parameters will be helpful for other findings in great apes and will also be suitable for further and precise determination of this parasite. The details distinguishing between male and female specimens are also stated and well defined. A comprehensive evaluation of the situation of Ascaris species parasitising orangutans, including a comparison with previously described orangutan parasite (i.e., A. satyri-species inquirenda), is discussed.
Keywords: internal transcribed spacer (ITS); Ascaris lumbricoides; non-human primates; ascarids; phylogeny reconstruction; cytochrome C oxidase I (CO1); host switching; species determination; Sumatran orangutan Pongo abelii